(untitled) (Research, Society and Development, 2021)
Clinostomum complanatum Rudolphi, 1814 is a digenetic trematode that infects mollusks, several species of freshwater fish and piscivorous birds. In its life cycle, C. complanatum has as its second intermediate host some freshwater fish, among which Jundiá (Rhamdia quelen). Thus, the aim of the present study was to evaluate the prevalence of Clinostomum infections in Jundiás captured in the estuary region of Pelotas/RS and to standardize a Polymerase Chain Reaction (PCR) to diagnose the presence of metacercariae in tissue samples from fish captured in this estuary. In the cross-sectional study and the standardization of PCR, 174 samples of Jundiás (Rhamdia quelen), captured by amateur fishermen at 5 different points in locations close to Laguna dos Patos, Lagoa Mirim or the São Gonçalo Channel were used. The prevalence of parasitism by Clinostomum spp. with diagnosis through parasitological keys was 36.21%, with variations in prevalence according to the reported capture points of specimens from Jundiá, being confirmed by standardized PCR. It is concluded that the prevalence is high in the analyzed silver catfish and PCR can be an auxiliary tool in the diagnosis of this parasite, increasing not only the sensitivity, but also the speed of the test. Such factors will be of great importance for future epidemiological studies, as well as for public health, since the consumption of freshwater fish, typical of oriental cuisine, is expanding in Rio Grande do Sul and Brazil.